PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL TWO STAY TWO STRAY(TSTS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 6 TALANG MANDI - Rizqy Nanda Arimurty; Rini Dian Anggraini; Suhermi Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This research aims to improve the learning process and improve learning outcomes of mathematics class of fifth SDN 6 Talang Mandi by implementing cooperative learning in the structural approach Two Stay Two Stray (TSTS). The subjects of the research were the fifth grade students SDN 6 Talang Mandi who have the heterogeneous academic ability. This research is a class act with two cycles. The first cycle consists of four times and one UH and the second cycle consists of three times and one UH. This research has four stages are planning, implementation, observation, and reflection. The result of the observation show the teachers and students activities have done after the action. Increasing the number of students who achieve at UH KKM in every end of each cycle compared to the number of the students who achieve a score of KKM on basic score. The results of this study indicate that application of cooperative learning in the structural approach TSTS can improve the process of learning and improve the learning outcomes of fifth grade of mathematics students at SDN 6 Talang Mandi in the odd semester of academic year 2013/2014.Keywords: Learning Process, Mathematics Learning Outcomes, Cooperative Learning, TSTS, Classroom Action Research.